New Directions In African Developmentalism: The Emerging Developmental State In Resource-Rich Africa - Ghebremusse, Sara (Journal of Sustainable Development Law and Policy, 2025)
African states are reclaiming a greater role in natural resource extraction that is generating significant scholarly interest and debate. This paper contributes to the debate by considering how these measures fit into the developmental state paradigm first used to study East Asian countries following World War II, and the “new” development state framework that currently dominates law and development scholarship. This paper argues that recent policy reforms by African states – including enhanced local participation, increased linkages between extractive industries and other sectors, and broader resource nationalist measures that seek to generate more revenue for national governments – are characteristic of the developmental state and “new” developmental state, neither have fully taken shape in resource-rich Africa as it is unclear how these new measures address “good governance” and democracy concerns.